Efekty synergii w działalności przedsiębiorstwa - Jonek-Kowalska, Izabela (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents the idea of synergy. In the next part, the author describes the method of identifying and quantifying synergy effects. After the presentation of the main idea, the usage of this method is adapted to the company throughout the process of joining the resources. At the end, the EVA is used as the best measure of synergy effects in the company. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 117-132